Youth-Participatory Visual Communication in Adolescent Substance Abuse Prevention: A Systematic Review - Agung Dwi Wicaksnono; Desi Dwi Prianti; Fitri Hariana Oktaviani (INJECT (Interdisciplinary Journal of Communication), 2025)
Adolescent substance abuse remains a persistent global public health concern, shaped by developmental vulnerability, social influences, and increasing exposure to media-based messages, highlighting the need for effective and contextually relevant prevention strategies. Although visual communication has become a prominent component of prevention campaigns, evidence regarding its effectiveness and the role of youth participation, particularly through Youth Participatory Action Research (YPAR), has not been systematically consolidated. This systematic literature review examines how visual communication is implemented in adolescent substance abuse prevention, evaluates its effectiveness in influencing knowledge, attitudes, social norms, and behaviours, and explores the contribution of YPAR to campaign design and impact. Following PRISMA and Kitchenham guidelines, a comprehensive search was conducted across Scopus and Google Scholar using PICO-informed keywords. Peer-reviewed studies published between 2015 and 2025 in English or Bahasa Indonesia were screened using predefined inclusion and exclusion criteria. Methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT), and data were synthesized through thematic analysis supported by NVivo 14. A total of 36 studies were included. The findings indicate that static visuals, audio-visual content, and social media–based strategies dominate the literature and are consistently associated with improvements in knowledge, risk perception, attitudes, and social norms. Behavioural outcomes were less frequently examined. Participatory and YPAR-driven visual approaches, although limited in number, demonstrated strong potential in fostering youth agency, engagement, and empowerment. These findings underscore the importance of integrating participatory visual communication strategies to enhance the relevance and effectiveness of adolescent substance abuse prevention efforts.